Rivaroxaban in patients with atrial fibrillation: from research to real practice (based on REGistry of Long-term AnTithrombotic TherApy-2 (REGATA)) - E. S. Kropacheva; E. N. Krivosheeva; E. P. Panchenko («REMEDIUM GROUP» Ltd., 2021)
Introduction. Despite the large evidence base for the use of rivaroxaban, cohort studies are interesting because shows the possibility of anticoagulant therapy in patients with high thromboembolic and bleeding risk and a burden of comorbidity in practice.Aim: to evaluate the efficacy and safety of rivaroxaban therapy in patients with atrial fibrillation in prospective REGATTA registry.Materials and methods. This study is a fragment of a single-center prospective REGATA registry (Registry of Long-term Antithrombotic Therapy (NCT043447187), conducted on the basis of the National Research Center of Cardiology of the Ministry of Health of the Russian Federation. 152 patients with high thromboembolic risk (median CHA2DS2-VASc = 4) received rivaroxaban therapy (median follow-up 1.5 years). The efficacy endpoint was the sum of cardiovascular complications (including cardiovascular death, ischemic stroke, and acute coronary syndrome). The safety endpoint bleedinds BARC types 2-5.Results. The frequency of cardiovascular events (combining cardiovascular death, ischemic stroke and acute coronary syndrome) was 5.8/100 patient-years. The use of a "reduced" dose of rivaroxaban was an independent predictor of the development of fatal cardiovascular complications. The rate of major bleeding was 3.7/100 patient-years, and the rate of clinical relevant bleedings was 19.4 /100 patientyears. The predictors of major/ clinical relevant bleedings were chronic kidney disease with a decrease in creatinine clearance of less than 50 ml/min and the anamneses of major/ clinical relevant bleedings.Conclusion. The main requirement for improving the safety of anticoagulants is follow up, focused in all changes in the cardiovascular and somatic status of the patient during treatment.